Control of the Stereochemical Course of [4+2] Cycloaddition during trans‐Decalin Formation by Fsa2‐Family Enzymes. (4th July 2018) - Kato, Naoki; Nogawa, Toshihiko; Takita, Ryo; Kinugasa, Kiyomi; Kanai, Misae; Uchiyama, Masanobu; Osada, Hiroyuki; Takahashi, Shunji
Abstract: Enzyme‐catalyzed [4+2] cycloaddition has been proposed to be a key transformation process in various natural product biosynthetic pathways. Recently Fsa2 was found to be involved in stereospecific trans ‐decalin formation during the biosynthesis of equisetin, a potent HIV‐1 integrase inhibitor. To understand the mechanisms by which fsa2 determines the stereochemistry of reaction products, we sought an fsa2 homologue that is involved in trans ‐decalin formation in the biosynthetic pathway of an enantiomerically opposite analogue, and we found phm7, which is involved in the biosynthesis of phomasetin. A decalin skeleton with an unnatural configuration was successfully constructed by gene replacement of phm7 with fsa2, thus demonstrating enzymatic control of all stereochemistry in the [4+2] cycloaddition. Our findings highlight enzyme‐catalyzed [4+2] cycloaddition as a stereochemically divergent step in natural product biosynthetic pathways and open new avenues for generating derivatives with different stereochemistry.